Design optimization of heterojunction 1T DRAM cell with SiGe body/drain for high performance. (1st December 2022) - Go, Seungwon; Kim, Shinhee; Lee, Dong Keun; Park, Jae Yeon; Park, Sora; Kim, Dae Hwan; Kim, Garam; Kim, Sangwan
Abstract: In this study, a heterojunction one-transistor (1T) dynamic random-access memory (DRAM) with SiGe body/drain has been proposed and its electrical characteristics have been investigated by technology computer-aided design simulation. The results reveal that the homojunction between body and drain with a narrow band gap material enhances not only retention characteristic but also write and erase efficiencies compared to those of the structure in which SiGe is only adopted at the body region. Consequently, the sensing margin of the optimized structure is ∼15.9 and ∼2.4 times larger than that of the Si and Si0.7 Ge0.3 -body 1T DRAM cells, respectively, with a retention time longer than 99 ms.